Analysis of Sublethal and Lethal Effects of Chlorantraniliprole on Loxostege sticticalis Based on Age-Stage, Two-Sex Life Table - Xiaoxue Pan; Yongmei Fan; Liangang Mao; Lizhen Zhu; Xingang Liu; Lan Zhang (Agriculture)
Chlorantraniliprole, serving as a substitute for traditional insecticide, has been widely utilized in controlling lepidopteran pests. Loxostege sticticalis (Lepidoptera: Crambidae) is a polyphagous insect and poses a significant threat as a migratory insect. This study investigated the life history traits of a field-collected population in response to chlorantraniliprole exposure based on an age-stage, two-sex life table. After treating the third-instar larvae of L. sticticalis with three different doses of chlorantraniliprole, namely LC10, LC25, and LC50, the survival, development, and fecundity of L. sticticalis were affected significantly in a dose-dependent manner. Chlorantraniliprole at doses of LC10, LC25, and LC50 prolonged the average generation time (T) compared to the control group. The net reproductive rate (R0) and intrinsic growth rate (r) were significantly higher in the LC10 group but significantly lower in the LC25 and LC50 groups. Chlorantraniliprole used at a dose of LC10 was shown to increase the finite growth rate (λ), while it decreased λ at doses of LC25 and LC50. These results suggested that chlorantraniliprole induces hormetic effects by enhancing fecundity and reproductive potential at lower sublethal concentration (LC10), while reducing the reproductive output at higher doses (LC25 and LC50). Our results provide useful information for developing management strategies for L. sticticalis involving the use of chlorantraniliprole.